The Role of Syekh Ismail Abdul Wahab in Islamic Education in Tanjungbalai City - Sirait, Andi Saputra; Al Farabi, Mohammad; Sapri, Sapri (Journal of Educational Sciences, 2025)
This study examines the contributions and role of Syekh Ismail Abdul Wahab in Islamic education in Tanjungbalai City. As a scholar and educator, he played a crucial role in establishing the Gubahan Islam educational institution and spreading Islamic values within the community. The aim of this study is to analyze Syekh Ismail’s intellectual journey, his contributions to Islamic education, and the challenges he faced in developing the Islamic education system. This research employs a historical method with a descriptive qualitative approach through literature studies, interviews with educational figures, and historical document analysis. The findings indicate that Syekh Ismail Abdul Wahab was not only an educator but also a leader who advocated for education based on tauhid and ethics. Despite challenges from Dutch colonial rule and limited resources, he remained committed to building an Islamic education system that continues to have an impact today. This study underscores the significant role of Islamic scholars in the development of Islamic education and provides new insights into the contributions of local figures in the history of education in Indonesia.